Modelo para un sistema tutorial en la facultad de diseño industrial de la Universidad Pontificia Bolivariana / Model for a Tutorial System at Industrial Design Faculty at the Universidad Pontificia Bolivariana - Suárez Peña, Juan José (Revista Internacional de Aprendizaje en la Educación Superior, 2015)
ABSTRACT It is determinant to decrease school desertion, academics mortality and the falling behind, to develop strategies that focuses on the professional education, the teacher’s formation, the academic loads, the pedagogical continuity and the insertion to the university life. We have found that a strengthened Sistema Tutorial makes easier a calmed and responsible transit of the students by the university life. We propose a Sistema Tutorial that accompanies the carrier selection, and the selection of the formation routes and curriculums, as the voluntary or mandatory development of extracurricular activities. We believe in a Sistema Tutorial that keeps feeding back not just the academics, but the cognitive, affective and social side of the student. RESUMEN Desarrollar estrategias alrededor de la orientación profesional, la formación de los docentes, la carga académi-ca, la continuidad pedagógica y la inserción a la vida universitaria, es determinante para disminuir la deserción escolar, la mortalidad académica y el rezago. Hemos encontrado que un Sistema Tutorial fortalecido posibilita un tránsito tranquilo y responsable de los estudiantes por la vida universitaria, un sistema que acompañe la elección de carrera, rutas de formación y planes de estudio, el desarrollo de actividades extracurriculares de carácter voluntario y/u obligatorio, a partir de una constante retroalimentación académica, cognitiva, afectiva y social. Contacto principal: paralelojuan@gmail.com